Dialog Lintas Iman Dalam Pemulihan Ekologis Pasca-Bencana: Studi Ekoteologi Multikultural di Aceh dan Sumatra - Ramdanil Mubarok; Sultan Sultan (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2026)
Natural disasters in Indonesia not only cause ecological damage but also profound social and spiritual impacts on multireligious communities. In Aceh and Sumatra, post-disaster recovery processes demonstrate that environmental reconstruction is inextricably linked to religious and multicultural dynamics. This study aims to analyze the role of interfaith dialogue in post-disaster ecological recovery using a multicultural ecotheology framework. This research employs a descriptive qualitative approach grounded in conceptual literature, analyzing academic works, theological documents, and socio-religious practices that have developed in the context of Aceh and Sumatra. The results indicate that interfaith dialogue functions as an ecotheological praxis that shapes collective ecological awareness, strengthens social solidarity, and integrates religious values ​with local wisdom in environmental recovery efforts. Collaborative interfaith practices such as reforestation, faith-based ecological education, and shared reflective rituals create a shared spiritual space that supports simultaneous social and ecological reconstruction. This study argues that the interfaith approach can be understood as a form of practical ecological theology that contributes to the development of socio-ecological peace in post-disaster communities. This research makes a theoretical contribution by offering a model of interfaith, multicultural ecotheology that is relevant to the development of contextual theology and ecological restoration policies in pluralistic societies.